Three Phase Power Converter with Bidirectional Power Flow Control for Electric Vehicle (EV) Charger - Tarasantisuk, Chanrit; Suyata, Thong-In (Journal of Advanced Development in Engineering and Science, 2023)
This paper presents the power converter three phase system with bidirectional power flow control for EV battery charger with connected power distribution. This research used the proportional plus resonant controller for regular stability controls of power converter in operation in charge mode and discharge mode. In the demonstrated bidirectional power flow control systems, the Hardware In the Loop (HIL) testing controlled with STM32F704VI microcontroller is used. Experimental results demonstrate a good performance for the controlled bidirectional power flow of the operation system and dc output loop of battery side.